Determination of the Durability of Polyurethane Coating on Mild Steel in Various Soil Media - K.O, Anyanwu; C.N, Anyakwo; A.I, Ndukwe; C, Onuoha; P.C, Agu (International Research Journal of Multidisciplinary Technovation, 2022)
In this paper, effort has been made to determine the durability of polyurethane coating on mild steel in acid, alkaline and neutral soil. A total of 42 mild steel coupons were used. Out of the 42 coupons, 21 were coated with polyurethane and the remaining 21 were left uncoated. Acid soil (pH = 4.5), Alkaline soil (pH =13.5) and neutral soil (pH = 6.8) were used as the test media. Seven each of the coated and uncoated coupons were buried in each soil media. On weekly basis, one coated and one uncoated coupon were withdrawn from each of the soil media and reweighed. The durability of the coating in each soil media was calculated using a proposed model. From the results obtained, the durability of polyurethane coating was found to be 7.0yrs, 4.5yrs and 2.9yrs in neutral, acid and alkaline soil respectively.